The effectiveness of transferring patients with open-angle glaucoma to therapy with a preservative-free fixed combination of a carbonic anhydrase inhibitor and a prostaglandin analogue - S. A. Korotkikh; G. V. Zhiborkin; A. S. Kozlova; E. S. Knyazeva; A. S. Shamkin (Российский офтальмологический журнал)
Purpose: to analyze the effectiveness of transferring open-angle glaucoma patients to therapy with a preservative-free fixed combination of a carbonic anhydrase inhibitor and a prostaglandin analogue. Material and methods. The study involved 58 people (24 men and 34 women), averagely aged 61.2 ± 7.1, diagnosed with stages II–III POAG and degree of compensation a-b (according to the Nesterov-Bunin classification). The patients were divided into three groups. Initally, Group 1 (22 people, 30 eyes) had received monotherapy with a beta-blocker (timolol), Group 2 (20 people, 27 eyes) had received monotherapy with the original prostaglandin analogue drug (latanoprost), and Group 3 (16 person, 19 eyes) had had therapy with the original drug, namely a fixed combination of a beta-blocker (timolol) and a prostaglandin analogue (latanoprost)). All patients were prescribed antihypertensive therapy with a fixed combination of a carbonic anhydrase inhibitor (dorzolamide) and a prostaglandin analogue (latanoprost) — the drug Dorzoprost, which was administered according to the standard regimen. We assessed the dynamics of intraocular pressure (IOP), perimetric indices, morphometric indicators of the optic nerve, tolerability of the drug regarding the effect on the ocular surface and safety regarding potential systemic side effects. Results. After 1 month of therapy, IOP significant decreased by 7.5 mm Hg (32 % of the initial value) in Group 1, by 3.7 mm Hg (19 %) in Group 2, and by 1 mm Hg (5 %) in Group 3. At month 3 and month 6, the hypotensive effect stabilized with respect to the previous control measurements (taken at 1 month) in all three groups. The morphometry of the optic nerve and the dynamics of perimetric indices showed no progression of glaucomatous optic neural opticopathy and no local or systemic undesirable effects of the therapy that could affect the compliance of the treatment. Conclusion. The Dorzoprost drug has demonstrated a high hypotensive efficiency when transferring patients from various basic therapy regimens and can be considered the drug of choice for patients with symptoms of keratoconjunctival xerosis and concomitant organ pathology requiring the use of systemic β-blockers.